Do shared goals really enhance team innovation? A review - Majdi Anwar Quttainah (International Journal of Management, Economics and Social Sciences (IJMESS), 2015)
This study aims to uncover the missing link between shared goals and team innovation. Previous literature reflects positive direct effects of shared goals on team innovative performance. This research serves as supplement to past studies. Minority dissent, teamwork behavior and team potency are introduced as mediators and knowledge diversity, climate for innovation and environmental dynamism as the mechanisms moderating the relationship between shared goals and team innovation. Contrary to previous studies, present review proposes that instead of only positive direct effect, shared goals may produce direct and indirect negative effects on team innovation. Specifically, under dynamic environment, shared goals may have little impact on innovation. In addition, shared goals may lead to less frequent occurrence of minority dissent, while minority dissent has proven positive impact on team innovation, especially in R&D teams.
Keywords: D2; O32; 330; Shared goals; team goals; team innovation; teamwork behavior; dynamic environment